KINERJA PENGELOLA BARANG MILIK DAERAH PADA PEMERINTAH DAERAH KABUPATEN MINAHASA - Rumbayan, Florah J.; Tulusan, Femmy; Tampongangoy, Deysi (Sam Ratulangi University, 2022)
This research aims to analyze and describe the performance of regional property managers in the Minahasa Regency local government. This research was conducted from October to December 2021. This research used descriptive qualitative methods to describe aspects related to the object of research in depth. The types of data used in this research are primary data and secondary data. The results of the research indicate that the quality of employees is still very lacking, especially in the field of Information and Technology with the constraints that occur are the sources of funding that are still lacking and have an impact on the limitations of existing equipment and resource capacity is still very lacking because they have not maximally understood the basic management of regional property and have not mastering Information and Technology. the quantity of work is good enough but not maximized because understanding of the duties and abilities of employees is still lacking so that in carrying out tasks there are still delays and still need direction from superiors. In Aspects of time use at work, employee attendance using a fingerprint system and monitored on time. Relations between fellow employees and superiors are well established and a conducive atmosphere is created. The initiative in carrying out the duties of employees is still waiting for orders/directions from superiors and still lacks initiative in doing things without prior instructions.